Sistem Pakar Untuk Mendiagnosa Penyakit Sistem Saraf Pusat Berbasis Web Dengan Menggunakan Metode Forward Chaining (Studi Kasus : Rumah Sakit Hermina Serpong Tangerang) - I.Gusti Ayu Melandra Putri; Hidayatullah Al Islami (CV. Multi Kreasi Media, 2024)
The nervous system is one of the organs that perform activities of a coordinating body. Central nervous system functions primarily to detect, analyze, process and deliver information. Sensory systems collect information which are processed in the brain and transmitted to the motor system to control the movement, visceral activity, and endocrine functions. All the action from the sensory and motor systems are controlled by nerves which are interconnected to form a network of signaling. Lack of information and knowledge about neurological causes many sufferers of neurological diseases. The methods used in this research is a method of Forward Chaining. The system to be built is a computer-based information system by utilizing the technology of artificial intelligence that serves as system tools or the giver of neurological diagnosis results to the user. Diagnoses generated by this system is equipped with a type of central nervous disease with pecegahan and the way of treatment. The system will analyze your answers to each question are given, so that the obtained results diagnoses based on the existing knowledge base in expert system. Research results in the form of expert system that can help users know what kind of diseases of the central nervous, giving information regarding central nervous disease and knowing how treatment and prevention.